2016
DOI: 10.1186/s13012-016-0521-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a large healthy lifestyle program: informing program implementation and scale-up in the prevention of obesity

Abstract: BackgroundThe Healthy Lifestyle Program for women (HeLP-her) is a low-intensity, self-management program which has demonstrated efficacy in preventing excess weight gain in women. However, little is known about the implementation, reach, and sustainability of low-intensity prevention programs in rural settings, where risk for obesity in women is higher than urban settings. We aimed to evaluate a low-intensity healthy lifestyle program delivered to women in a rural setting to inform development of effective com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Mixed methods have been used in Hybrid 2 designs to evaluate both process and outcomes of program effectiveness and implementation (19, 50, 78). For instance, Hamilton and colleagues (40) studied an evidence-based quality improvement approach for implementing supported employment services at specialty mental health clinics in a site-level controlled trial at four implementation sites and four control sites.…”
Section: Illustrations Of Mixed Methods Designs In Evaluation Researchmentioning
confidence: 99%
“…Mixed methods have been used in Hybrid 2 designs to evaluate both process and outcomes of program effectiveness and implementation (19, 50, 78). For instance, Hamilton and colleagues (40) studied an evidence-based quality improvement approach for implementing supported employment services at specialty mental health clinics in a site-level controlled trial at four implementation sites and four control sites.…”
Section: Illustrations Of Mixed Methods Designs In Evaluation Researchmentioning
confidence: 99%
“…While little evidence has been generated in the dissemination and implementation of childhood obesity research, there are key similarities between our findings and those reported in adult dissemination and implementation trials for obesity research. For example, Kozica et al [ 18 ] reported on the successful implementation of a healthy lifestyle programme in rural settings, noting the importance of organisational and local stakeholder involvement and buy-in to the programme. In addition, Damschroder et al [ 19 , 20 ] found that the dissemination of a weight management programme in Veterans Affairs Hospitals was strongly dependent on organisational characteristics, and that, in some situations, local champions could overcome organisational barriers.…”
Section: Discussionmentioning
confidence: 99%
“…MSPs are used across different domains that affect livelihoods such as natural resource management (Faysse, 2006;Warner, 2006a), sustainable intensification (Schut et al, 2016c), environmental management (Kaiser et al, 2016), disaster management (Djalante, 2012), and health services (Vassal et al, 2015;McHugh et al, 2016). Moreover, they are applied as part of different intervention types such as policies (Hale and Mauzerall, 2004;Rothenberger et al, 2005;Kefasi et al, 2011;Beers and Geerling-Eiff, 2014), programs (Adekunle and Fatunbi, 2012;Kozica et al, 2016), and projects (Kilelu et al, 2013;Kaiser et al, 2016), which are further discussed in the following section.…”
Section: Why Study the Contribution Of Msps To R4d Interventions?mentioning
confidence: 99%
“…Over the past decade, MSPs have been used to mobilize diverse stakeholders to identify and analyze problems, and to design and implement R4D activities to overcome these problems. Although MSPs are 'branded' differently -as multi-level community partnerships (Kozica et al, 2016;Dickson-Gomez et al, 2016), public-private partnerships (Eggersdorfer and Bird, 2016;Yildirim et al, 2016;Abbott, 2012), multi-stakeholder partnerships (Biermann et al, 2007;Kefasi et al, 2011), multi-stakeholder platforms (Huang et al, 2017;de-Zeeuw, 2010;Thiele et al, 2011), innovation platforms (Kilelu et al, 2013;Schut et al, 2016b;King et al, 2010), and learning alliances (Verhagen et al, 2008;Douthwaite et al, 2003) -they are all used to facilitate the involvement of different stakeholders in interventions, thereby enhancing the impact of the interventions on livelihoods.…”
Section: Introductionmentioning
confidence: 99%